2019
DOI: 10.1002/mp.13393
|View full text |Cite
|
Sign up to set email alerts
|

Internal radiation dose assessment of radiopharmaceuticals prepared with cyclotron‐produced 99mTc

Abstract: Purpose Technetium‐99m (99mTc) is the radioisotope most widely used in diagnostic nuclear medicine. It is readily available from 99Mo/99mTc generators as the β−decay product of the 99Mo (T½ = 66 h) parent nuclide. This latter is obtained as a fission product in nuclear reactors by neutron‐induced reactions on highly enriched uranium. Alternative production routes, such as direct reactions using proton beams on specific target materials [100Mo(p,2n)99mTc], have the potential to be both reliable and relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 20 publications
0
15
0
4
Order By: Relevance
“…In their studies [15] and [20], Hou et al reported that at proton beam energies below 20 MeV, the contents of [94][95][96][97] Mo contribute more than the content of 98 Mo to the dose increase and image quality degradation. Recent studies by [24,25] figure 10.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In their studies [15] and [20], Hou et al reported that at proton beam energies below 20 MeV, the contents of [94][95][96][97] Mo contribute more than the content of 98 Mo to the dose increase and image quality degradation. Recent studies by [24,25] figure 10.…”
Section: Resultsmentioning
confidence: 99%
“…The 98 Mo DCC should also be considered if the proton beam energies are greater than 20 MeV, which is the threshold for the 98 Mo(p,3n) 96 Tc and 98 Mo(p,3n) 96m Tc reactions [14,36]. 96m Tc deexcites to 96 Tc with 98% probability [37], and 96 Tc is reported to be one of the major impurities affecting the radiation dose and image quality [15,20,24,25]. Therefore, the 99.815% and 99.86% enriched 100 Mo products, whose 98 Mo DCCs as well Table 3.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although, all the accelerator-based strategies are under development as major alternatives but the issues related to the practical limits of irradiation volumes and low crosssections of the reaction routes need careful assessment [3]. For example, the direct 99m Tc production from protonbombarded 100 Mo-enriched targets using cyclotron is considered as reliable and cost-effective alternative production routes [32]. Qaim et al [33] reported that the ratio of atoms of long-lived 99g Tc and 98 Tc to those of 99m Tc is appreciably higher in cyclotron production than in generator production of 99m Tc.…”
Section: Comparison Of 99 Mo Production Processmentioning
confidence: 99%